Effect of coil turns in 4-coils system for mid-range wireless power transfer - Tan S.Y.; Lee H.J. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric fields; Energy transfer; Receivers (containers); Secondary batteries; Thermoelectric equipment; Transmitters; Battery drains; Electronic device; Magnetic and electric fields; Number of turns; Resonance structure; Transmission medium; Transmitter and receiver; Wireless power transfer; Inductive power transmission